2016
DOI: 10.3892/etm.2016.3699
|View full text |Cite
|
Sign up to set email alerts
|

Excisional keratectomy combined with focal cryotherapy and amniotic membrane inlay for recalcitrant filamentary fungal keratitis: A retrospective comparative clinical data analysis

Abstract: The aim of the present study was to investigate the efficacy of a novel surgical intervention, excisional keratectomy combined with focal cryotherapy and amniotic membrane inlay (EKCAI), for the treatment of recalcitrant filamentary fungal keratitis. A retrospective analysis was performed of patients who underwent excisional keratectomy combined with conjunctival flap inlay (EKCFI), EKCAI or therapeutic penetrating keratoplasty (TPK) from January 2006 to January 2011. Recalcitrance was determined as being unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(43 reference statements)
0
9
1
Order By: Relevance
“…The rate of healing with ISVCZ in our study (95%) corresponded with that of multiple previous studies reporting success rates of 66.6 to 100% with the same agent in recalcitrant fungal keratitis. 4 , 5 , 17 , 18 , 19 However, this was in contrast to a recent study by Narayana et al, who demonstrated no added advantage of ISVCZ in the management of moderate to severe fungal corneal ulcers. 20 We believe these conflicting results could be explained by the ethnic variability and regional differences in microbiological profile in both studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The rate of healing with ISVCZ in our study (95%) corresponded with that of multiple previous studies reporting success rates of 66.6 to 100% with the same agent in recalcitrant fungal keratitis. 4 , 5 , 17 , 18 , 19 However, this was in contrast to a recent study by Narayana et al, who demonstrated no added advantage of ISVCZ in the management of moderate to severe fungal corneal ulcers. 20 We believe these conflicting results could be explained by the ethnic variability and regional differences in microbiological profile in both studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Various other interventions, such as penetrating keratoplasty (PKP), collagen crosslinking with photoactivated riboflavin (PACK-CXL), excisional keratectomy combined with focal cryotherapy and amniotic membrane inlay, have been proposed to deal with these cases. [2][3][4] However, these have their own limitations and targeted delivery of antifungal agents at the ulcer site by means of intrastromal injections remains an effective alternative of bypassing these complex options. 5,6 These injections are known to enhance the drug levels at the desired site of the cornea thereby allowing successful healing of the corneal ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…Thermotherapy has been used to treat deep fungal infections, namely, sporotrichosis, chromomycosis, and even candidal keratitis. [3][4][5] Cryotherapy in CI has not been reported in PubMed in English language. The exact mechanism of cryotherapy for treatment of CI is unclear.…”
Section: Liquid Nitrogen Cryotherapy For Chronic Recalcitrant Interdimentioning
confidence: 99%
“…It may be speculated that on rapid cooling, formation of intracellular ice crystals induces dehydration and pH changes, disrupting the infected cells along with Candida spp. 4,5 Slow thawing leads to prolonged exposure to toxic substrates during recrystallization, which increases cell damage. Cryotherapy may also cause denaturation of fungal cell wall proteins.…”
Section: Liquid Nitrogen Cryotherapy For Chronic Recalcitrant Interdimentioning
confidence: 99%
See 1 more Smart Citation